2012
DOI: 10.1080/10942912.2010.551308
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and Anti-Glycation Activity of Buckwheat Hull Tea Infusion

Abstract: The utilization of buckwheat hull for the preparation of buckwheat hull tea was addressed in this study. The total phenolics content, flavonoids profile, antioxidant capacity, and antiglycation activity of buckwheat hull tea were compared to those of green tea. The buckwheat hull contained rutin, quercetin, and C-glucoflavones; however, the total phenolic content was significantly lower in comparison to green tea leaves. Rutin and vitexin were the main flavonoids found in buckwheat hull tea. The buckwheat hull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…It was reported that the TPC in common and tartary buckwheat hulls and bran were higher than in the flour, while the TPC of tartary buckwheat bran and flour were higher than in common buckwheat [20]. Moreover, Zielinska et al [34] prepared tea from the buckwheat hulls to examine its TPC, TFC, antioxidant capacity, and anti-glycation activity. Results indicated that the number of phenolic compounds extracted with 80% methanol from dry buckwheat hulls (3.56 ± 0.19 mg/g) was 64 times lower than that of green tea leaves.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the TPC in common and tartary buckwheat hulls and bran were higher than in the flour, while the TPC of tartary buckwheat bran and flour were higher than in common buckwheat [20]. Moreover, Zielinska et al [34] prepared tea from the buckwheat hulls to examine its TPC, TFC, antioxidant capacity, and anti-glycation activity. Results indicated that the number of phenolic compounds extracted with 80% methanol from dry buckwheat hulls (3.56 ± 0.19 mg/g) was 64 times lower than that of green tea leaves.…”
Section: Resultsmentioning
confidence: 99%
“…The greatest ACE inhibitory activity (IC50 = 30 μg/mL) was found for the extracts of buckwheat hulls (Tsai et al, 2012). These finding suggest the impact of polyphenols on ACE inhibitory activity, because hull is a rich source of 10.2478/aucft-2020-0019 of biscuits prepared from roasted buckwheat flour fermented by lactic acid bacteria flavonoids and phenolics acids (Zielińska et al, 2013). Recently it was found that lentil polyphenol extract prevents angiotensin II-induced hypertension, vascular remodeling and perivascular fibrosis (Yao et al 2012).…”
Section: Introductionmentioning
confidence: 87%
“…In addition, fermentation by-products as pineapple stem waste obtained during bromelain manufacturing process and buckwheat hull tea have also been described as inhibitors on the formation of AGE (118)(119)(120) .…”
Section: Food Reformulationmentioning
confidence: 99%